Utility of illness symptoms for predicting COVID-19 infections in children - Geena Y. Zhou; Nicole Y. Penwill; Grace Cheng; Prachi Singh; Ann Cheung; Minkyung Shin; Margaret Nguyen; Shalini Mittal; William Burrough; Mia-Ashley Spad; Sarah Bourne; Naomi S. Bardach; et al. (BMC, 2022)
Abstract Background The Centers for Disease Control and Prevention and the American Academy of Pediatrics recommend that symptomatic children remain home and get tested to identify potential coronavirus disease 2019 (COVID-19) cases. As the pandemic moves into a new phase, approaches to differentiate symptoms of COVID-19 versus other childhood infections can inform exclusion policies and potentially prevent future unnecessary missed school days. Methods Retrospective analysis of standardized symptom and exposure screens in symptomatic children 0-18 years tested for SARS-CoV-2 at three outpatient sites April to November 2020. Likelihood ratios (LR), number needed to screen to identify one COVID-19 case, and estimated missed school days were calculated. Results Of children studied (N = 2,167), 88.9% tested negative. Self-reported exposure to COVID-19 was the only factor that statistically significantly increased the likelihood of a positive test for all ages (Positive LR, 5-18 year olds: 5.26, 95% confidence interval (CI): 4.37-6.33; 0-4 year olds: 5.87, 95% CI: 4.67-7.38). Across ages 0-18, nasal congestion/rhinorrhea, sore throat, abdominal pain, and nausea/vomiting/diarrhea were commonly reported, and were either not associated or had decreased association with testing positive for COVID-19. The number of school days missed to identify one case of COVID-19 ranged from 19 to 48 across those common symptoms. Conclusions We present an approach for identifying symptoms that are non-specific to COVID-19, for which exclusion would likely lead to limited impact on school safety but contribute to school-days missed. As variants and symptoms evolve, students and schools could benefit from reconsideration of exclusion and testing policies for non-specific symptoms, while maintaining testing for those who were exposed.